The relationship between visible thrombus aspiration material with no-reflow and in-hospital mortality ratio in patients with anterior ST-elevation myocardial infarction treated with primary percutaneous coronary intervention - Taner Şeker; Caner Türkoğlu; Oğuz Akkuş; Mustafa Gür (KARE Publishing, 2019)
Objective: The benefit of intracoronary thrombus aspiration (TA) during primary percutaneous coronary intervention (pPCI) in patients with ST-segment elevation myocardial infarction (STEMI) is not yet fully clear. The aim of this study was to investigate the clinical impact of visible thrombus aspiration (VTA) material. Methods: A total of 295 patients with a Thrombolysis in Myocardial Infarction (TIMI) flow score of 0 or 1 after an anterior STEMI were included in the study. Manual TA devices were used before performing PCI. The patients were divided into 2 groups: (1) visible thrombus aspiration (VTA) group and (2) non-visible thrombus aspiration (non-VTA) group. No-reflow was defined as TIMI grade 0, 1, or 2 flow, or TIMI grade 3 with a myocardial blush of grade 0 or 1. The primary endpoint was the occurrence of no-reflow. Results: VTA was retrieved in 178 (60.3%) of the patients. A no-reflow determination was significantly less frequent in the VTA group (p<0.001). The ejection fraction and ST-segment resolution values were higher, and the in-hospital mortality, Killip class II-IV rating, and post-pPCI TIMI frame count were lower in the VTA group (p<0.05 for each). Conclusion: VTA predicted a lower rate of in-hospital mortality and no-reflow in patients with anterior STEMI who underwent pPCI.